Wellness Tourism : Profil dan karakteristik Spa di Kawasan Wisata Ubud, Gianyar - Kiskenda, Dewa; Trimandala, Agus; Wiradinata, Wahyu (Universitas Pendidikan Ganesha, 2024)
Ubud actively participate in providing Spas, but not identified yet empirically the profile of Spa product. This profile will be measured by identifying the characteristics of the product of Spas and identify the characteristics of tourist who used Spa. Using a qualitative descriptive analysis with number of samples as much as 42 informants and 30 samples of respondents tourist were accidental sampling purporsive. 96 businesses Spa those are 73 Day Spas and 23 Spas of Hotel/Resort spreaded in (1) Kelurahan Ubud, (2) Desa Campuan, (3) Desa Kedewatan. Products Spas in Ubud is still dominated by traditional Balinese spa products and Spa products that collaborated with other traditionaly concepts that customized with tourist needs / demand. The tourist users of spa product, travelers are dominated by old age and the age of the baby boomber with various types of professions, gender, status, region of origin and educational background with income 500 - 5000 per month, travelers who have experience and have known spa products, as well as tourists who want to indulge themselves with relaxation, deal with stress with an interest in the product Spas Ubud that offered by Spa traditional Balinese